A novel reliable and secure communication scheme for cognitive radio networks using concatenated kernel codes. (7th February 2018) - Pavan Kumar, C.; Selvakumar, R.
Summary: Cognitive radio networks have emerged as a possible solution for the spectrum scarcity problem. Cognitive radio networks involve heterogeneous entities as part of it for facilitating spectrum sharing. Ensuring reliability and security in such scenario is inevitable for the licensed users (primary users) as well as for the unlicensed users (secondary users). To address the challenges of reliable and secure communication for the secondary users, in this paper, a novel reliable and secure communication framework is proposed. A class of group codes called concatenated kernel codes is used to achieve reliability and techniques of fundamental cutset and fundamental circuit to achieve security in terms of authentication of sender. It is shown that the proposed communication framework provides reliability mitigating the continuous interference of primary users and security by defending against the cryptanalytic attacks such as replay attack, related key attack, and man‐in‐the‐middle attacks. The theoretical basis of the proposed framework is validated, and its performance is evaluated through simulations. Abstract : Secondary users in cognitive radio networks are subjected to continuous interference from primary users, due to frequency hopping and also from the intruders present in the channel. To overcome these challenges, a novel communication framework is defined using techniques of coding theory and graph theory. Reliability to communicate over cognitive radio networks is achieved by using a class of group codes called concatenated kernel codes and security by using fundamental circuit and fundamental cutset defined over minimum trellis of concatenated kernel codes.